Capitalism and Democracy: A Critical & Investigative Analysis of the United States Government’s Policy Making - Hamzaee, Reza G.; Guy, Alec; Ryan, Brock (Archives of Business Research, 2017)
Policy making, put in place by the people for the purpose of serving the people, should be one of, if not the, most efficient institutions in the nation. In this research paper, the authors seek to critically evaluate U.S. policymaking and its efficiency. Currently, the policymaking process attempts to blend both democratic values and capitalistic traits. Disturbing habits, such as proposing omnibus, complicated bills proposed just before important deadlines, are being routinely practiced in congress. Negative externalities exist in the presence of extensive government regulation which ends up hurting the market it intended to help, and it is wasting taxpayers’ money. This research also points out worrisome trends in the United States economy, such as the continued growth of the wealth gap and the lack of a fair minimum wage as well as any specific policy targeting an effective employability enhancement. Current legislatures have made no serious attempt to tackle either of these issues, and the authors explain why this is such a serious problem. The goal of the authors is to challenge the current policymaking process in hopes that recognition of its shortfalls may bring about changes in that process.